Alloy Design and Microstructure Evolution in the AlxCoCrFeNi Alloy System Synthesized by Laser Metal Deposition - Kuczyk, Martin; Kotte, Liliana; Kaspar, Jörg; Zimmermann, Martina; Leyens, Christoph (Frontiers in Materials, 2020)
In this contribution the AlxCoCrFeNi alloy system is explored thoroughly over a wide compositional range of x = 0.2 to 1.5 (5 to 30 at% Al). For this alloy system compositional gradient structures were produced by laser metal deposition of pre-alloyed CoCrFeNi and elemental Al powders using an in-house developed coaxial cladding system COAXpowerline . The evolution of the microstructure with increasing Al content was analyzed in the as built as well as the homogenized condition (1350 K for 20 h). Metallographic cross sections were prepared and thoroughly analyzed by means of scanning electron microscopy, energy dispersive X-ray spectroscopy and electron backscattered diffraction. Additionally, the evolution of the sample hardness with increasing Al contents was determined for both sample conditions. In the AlxCoCrFeNi alloy system the lattice structure as well as the sample hardness can easily be adjusted by the variation of Al. With increasing Al content a phase transition from a solid solution fcc phase towards a multiphase bcc microstructure consisting of a Fe and Cr rich solid solution bcc phase and an ordered Al and Ni rich bcc B2 phase can be observed. This is combined with an increase in sample hardness from around 200 HV up to around 500 HV in the as built condition. The regions of phase transition for both sample conditions were compared to ab initio thermodynamic calculations done using a CALPHAD approach. For the as built condition a strong deviation from the calculated transition regime could be observed. After homogenization the experimental and calculated data are in good agreement.